La représentation du chat en français - Cholewa, Joanna (Studia Romanica Posnaniensia, 2007)
In the article, we try to examine a set of features attributed by users of French to a cat. Since there are more than one image of the world in natural languages, we wanted to show to what extent the linguistic image of a cat, considered as a fragment of extralinguistic reality, differs from an encyclopaedic image of this animal. We proved that these images are complementary and not contradictory (with one exception). Nevertheless, the number of their distinctive features is considerable.